发布网友 发布时间:2024-10-23 22:21
共2个回答
热心网友 时间:2025-01-14 18:40
2)n
s(n-1)=(-3/2)(n-1)^2+(205/2n^2+205/2n,求数列{an}的通项公式
sn=(-3/2)n^2+(205/2)n^2+(205/2)n]-[(-3/2)(n-1)^2+(205/2)*1^2+205/2*1=101适合an=-3n+104
∴数列的通项公式an=-3n+104(n>=1;2)(n-1)
an=sn-s(n-1)
=[(-3/2)(n-1)]
=-3n+104(n>1)
又a1=s1=(3/已知数列{an}前n项的和sn=-3/
热心网友 时间:2025-01-14 18:40
一。an=Sn-S(n-1)=2n^2+2n-2(n-1)^2-2(n-1)=4n
二。根据条件:b(n+1)=bn+4n
所以:bn-b(n-1)=4(n-1)......(1)
b(n-1)-b(n-2)=4(n-2)......(2)
b3-b2=4X2......(n-2)
由(1)+(2)+......+(n-2)得:bn-2=4(n-1+2)(n-2)/2=2(n-2)(n+1)
又b2=b1+a1=1+5=5
所以:bn=2n^2-2n+1